2022
DOI: 10.3233/jifs-210981
|View full text |Cite
|
Sign up to set email alerts
|

The convergence level and influencing factors of China’s digital economy and real economy based on grey model and PLS- SEM

Abstract: The paper constructs a research model mainly based on the Deng’s correlation analysis model on the convergence level measurement, the GM (1,1) coordinated development prediction model and PLS-Structural Equation Model (PLS-SEM) analysis model on the influencing factors. The data about China’s digital economy and real economy from 2005 to 2019 (totaled 2,250) is adopted to conduct an empirical analysis of the convergence level from 2005 to 2019 and predict the development trend from 2020 to 2029. The paper coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Let X (0) = ( x (0) (1), x (0) (2),…, x (0) ( n )) be the original data series and X (1) = ( x (1) (1), x (1) (2),…, x (1) ( n )) be the first-order accumulating data series, where x (1) ( k ) can be calculated as follows based on the first-order accumulating generation operator (1-AGO) [ 34 ]. where x (0) ( k ) indicates the original data, and x (1) ( k ) indicates the 1-AGO data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Let X (0) = ( x (0) (1), x (0) (2),…, x (0) ( n )) be the original data series and X (1) = ( x (1) (1), x (1) (2),…, x (1) ( n )) be the first-order accumulating data series, where x (1) ( k ) can be calculated as follows based on the first-order accumulating generation operator (1-AGO) [ 34 ]. where x (0) ( k ) indicates the original data, and x (1) ( k ) indicates the 1-AGO data.…”
Section: Methodsmentioning
confidence: 99%
“…Assume the matrix X (1) accords with the exponential change law, and the whitenization equation of the GM(1,1) model is shown as follows [ 34 ]. where t indicates the time; a indicates the developing coefficient; and b indicates the grey input.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Andrei et al used sigma convergence analysis to study the gaps between 28 countries of the European Union, and the research showed that the gaps were gradually narrowing [29]. Xu et al analyzed the convergence level using the data from 2005 to 2009 and predicted the future trend [30]. Park et al studied the digital divide phenomenon in 108 countries, classified the level of digital convergence into three categories and proposed targeted recommendations [31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Actively exploring the mechanism and path of the digital economy to realize the structural adjustment and optimization of the sports industry is an inevitable move to realize the high-quality development of China's sports industry under the new normal [7][8]. Based on the domestic perspective, the sports industry belongs to the real economy, and the continuous development and innovation of digital technology have strengthened the integration and development of the digital economy with the real economy in a wider range, a deeper level, and a wider field [9][10].…”
Section: Introductionmentioning
confidence: 99%